2015
DOI: 10.1080/15384047.2015.1070980
|View full text |Cite
|
Sign up to set email alerts
|

KIFC1 is a novel potential therapeutic target for breast cancer

Abstract: Kinesin-like protein KIFC1, a normally nonessential kinesin motor, plays a critical role in centrosome clustering in cancer cells and is essential for the survival of cancer cells. Herein, we reported that KIFC1 expression is up-regulated in breast cancer, particularly in estrogen receptor negative, progesterone receptor negative and triple negative breast cancer, and is not associated with epidermal growth factor receptor 2 status. In addition, KIFC1 is highly expressed in all 8 tested human breast cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 21 publications
(31 reference statements)
5
83
0
1
Order By: Relevance
“…For example, KIFC1 is upregulated in human breast cancer [19], whereas KIF2C is upregulated in esophageal squamous cell carcinoma and is associated with poor prognosis [22]. KIF14 expression is significantly increased in cervical tumor tissues, and its expression is positively associated with a high tumor stage, lymph node metastasis, and chemoresistance [23].…”
Section: Discussionmentioning
confidence: 99%
“…For example, KIFC1 is upregulated in human breast cancer [19], whereas KIF2C is upregulated in esophageal squamous cell carcinoma and is associated with poor prognosis [22]. KIF14 expression is significantly increased in cervical tumor tissues, and its expression is positively associated with a high tumor stage, lymph node metastasis, and chemoresistance [23].…”
Section: Discussionmentioning
confidence: 99%
“…Kinesin like protein (KIFC1), a unique mitotic kinesin, has recently emerged as an new anti-cancer drug target (17). Increased centrosome number, or centrosome amplification, has been reported in a variety of human primary cancers and correlates with aneuploidy, chromosomal instability and tumorigenesis (1822).…”
Section: Introductionmentioning
confidence: 99%
“…reported that KIFC1 is overexpressed in human breast cancers, and that KIFC1 overexpression correlates to increased aggressiveness and poorer clinical outcomes in breast cancer patients (26). Recently, we also demonstrated that KIFC1 expression is up-regulated in breast cancer, particularly in triple negative breast cancer (TNBC), and that KIFC1 is highly expressed in human breast cancer cell lines, but is undetectable in primary normal human mammary epithelial cells and weakly expressed in two human fibroblast lines (17). We further showed that KIFC1 silencing significantly reduced breast cancer cell viability (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, co-immunoprecipitation results of PJ34 and KIFC1 have yet to be reported. Due to the fact that the KIFC1 mRNA level is shown to be significantly diminished in various PJ34 treated breast cancer cell lines [110], we speculate that PJ34 might be transcriptionally suppressing the expression of KIFC1 given that PARP has been formerly reported to be a transcriptional regulator [111]. …”
Section: Chemotherapies Against Kifc1mentioning
confidence: 99%